The ethoxycarbonyl group as both activating and protective group in N-acyl-Pictet–Spengler reactions using methoxystyrenes. A short approach to racemic 1-benzyltetrahydroisoquinoline alkaloids - Keller, Marco; Sauvageot-Witzku, Karl; Geisslinger, Franz; Urban, Nicole; Schaefer, Michael; Bartel, Karin; Bracher, Franz (Beilstein Journal of Organic Chemistry, 2021)
We present a systematic investigation on an improved variant of the N-acyl-Pictet–Spengler condensation for the synthesis of 1-benzyltetrahydroisoquinolines, based on our recently published synthesis of N-methylcoclaurine, exemplified by the total syntheses of 10 alkaloids in racemic form. Major advantages are a) using ω-methoxystyrenes as convenient alternatives to arylacetaldehydes, and b) using the ethoxycarbonyl residue for both activating the arylethylamine precursors for the cyclization reaction, and, as a significant extension, also as protective group for phenolic residues. After ring closure, the ethoxycarbonyl-protected phenols are deprotected simultaneously with the further processing of the carbamate group, either following route A (lithium alanate reduction) to give N-methylated phenolic products, or following route B (treatment with excess methyllithium) to give the corresponding alkaloids with free N–H function. This dual use of the ethoxycarbonyl group shortens the synthetic routes to hydroxylated 1-benzyltetrahydroisoquinolines significantly. Not surprisingly, these ten alkaloids did not show noteworthy effects on TPC2 cation channels and the tumor cell line VCR-R CEM, and did not exhibit P-glycoprotein blocking activity. But due to their free phenolic groups they can serve as valuable intermediates for novel derivatives addressing all of these targets, based on previous evidence for structure–activity relationships in this chemotype.
Keywords: acyl Pictet–Spengler reaction; alkaloids; antiproliferative activity; benzyltetrahydroisoquinolines; ion channels; protective group; total synthesis